A Model for Increasing the Fidelity and Effectiveness of Interventions for Challenging Behaviors. Issue 1 (January 2015) - Dunlap, Glen; Lee, Janice K.; Joseph, Jaclyn D.; Strain, Phillip
<x xml:space="preserve">Abstract</x> A need exists for intervention strategies that are both effective in reducing challenging behaviors and practical for use by typical practitioners of early childhood care and education. In this article, we describe a model, Prevent–Teach–Reinforce for Young Children, which is based on extensive research and includes features designed to enhance fidelity of implementation by teachers and child care staff of toddlers and preschoolers. The article includes descriptions of the steps in the model and case stories that illustrate the model's implementation.